Serum ammonia variation predicts mortality in patients with hepatitis B virus-related acute-on-chronic liver failure - Cai, Yi-Jing; Dong, Jia-Jia; Chen, Rui-Cong; Xiao, Qian-Qian; Li, Xu-Mei; Chen, De-Yuan; Cai, Chao; Lin, Xiu-Li; Shi, Ke-Qing; Lu, Ming-Qin (Frontiers in Microbiology, 2023)
Background: Hyperammonemia is critical to the development of hepatic encephalopathy (HE) and is associated with mortality in end-stage liver disease. This study investigated the clinical value of ammonia variation in hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) patients.Methods: A total of 276 patients with HBV-ACLF were retrospectively recruited. Patients' ammonia levels were serially documented. Baseline ammonia, Peak ammonia (Highest level), and Trough ammonia (Lowest level) were particularly corrected to the upper limit of normal (AMM-ULN). The primary endpoint was 28-day mortality.The 28-day, 3-month, and 12-month mortality were 19.2%, 25.7%, and 28.2%, respectively. 51 (18.4%) patients had overt HE (grade 2/3/4). Peak AMM-ULN was significantly higher in patients with overt HE and non-survivors compared with their counterpart (P < 0.001). Following adjustment for significant confounders, high Peak AMM-ULN was an independent predictor of overt HE (hazard ratio,1.031, P < 0.001) and 28-day mortality (hazard ratio,1.026, P < 0.001). The cut-off of Peak AMM-ULN was 1.8 determined by using X-tile. Patients with Peak AMM-ULN appearing at day 1-3 after admission had a higher proportion of overt HE and mortality compared to other groups. Patients with decreased ammonia levels within 7 days had better clinical outcomes than those with increased ammonia.Conclusions: Serum Peak ammonia was independently associated with overt HE and mortality in HBV-ACLF patients. Serial serum ammonia may have prognostic value.